Diagnostic importance of faecal markers in long-term monitoring of anti-TNF- therapy in primary responders with Crohn’s disease - Łykowska-Szuber, Liliana; Klimczak, Katarzyna; Eder, Piotr; Krela-Kaźmierczak, Iwona; Stawczyk-Eder, Kamila; Michalak, Michał; Studniarek, Adam; Kościński, Tomasz; Szymczak, Aleksandra; Linke, Krzysztof (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: Monitoring the response to biological treatment in Crohn’s disease (CD) is a very important element of the therapeutic optimisation. Aim : To evaluate the usefulness of measuring calprotectin, lactoferrin, and myeloperoxidase in stool as markers of long-term clinical and endoscopic response to anti-tumour necrosis factor α (anti-TNF) treatment in CD. Material and methods : The studied group consisted of 35 CD patients treated with anti-TNF-α antibodies. Clinical activity was evaluated using Crohn’s Disease Activity Index (CDAI), and the exacerbation of endoscopic changes was evaluated using a Simple Endoscopic Score for Crohn’s Disease (SES-CD). The concentration of calprotectin, lactoferrin, and myeloperoxidase was measured using the ELISA method. All measurements were performed three times – before, after 3 months, and after a year of therapy. Results : During anti-TNF treatment the concentrations of all measured faecal markers decreased significantly in relation to baseline values. We observed a significant correlation at all time-points: before the therapy, after 3 months, and 12 months after starting the therapy, between the concentration of calprotectin and SES-CD, calprotectin and CDAI, as well as between lactoferrin and SES-CD, and lactoferrin and CDAI. Myeloperoxidase correlated with both SES-CD and CDAI only after 1 year of treatment. Conclusions : Faecal calprotectin and lactoferrin are valuable markers of clinical and endoscopic activity of CD in patients treated with anti-TNF antibodies. They are useful in monitoring the response to treatment. The usefulness of myeloperoxidase in this respect remains controversial.